Education on Giving Leaflets and The Potential of Karamunting Leaves (Rhodomyrtus Tomentosa) Herbal Efficacious in Society - M. Andi Chandra; Muhammad Hidyatullah (Asosiasi Profesi Multimedia Indonesia, 2023)
Coronavirus disease (COVID-19) is spreading rapidly throughout the world including Indonesia. The use of herbal medicinal plants has increased since the Corona Virus Disease (COVID-19) pandemic, one of which is karamunting leaves. The methods used include: Field observations, we recorded the number of residents, their work and the plants that grow in the yard so that they can provide education to the community, especially in the North Landasan Ulin Village, Lianganggang District, Banjarbaru City. The results of the initial observation activities were carried out to look for problems in the community, the problems encountered by the community service team were the lack of public knowledge about plants that have the potential for traditional medicinal properties. Planting in the yard of the house has a characteristic as an herbal medicine. The conclusion from this activity was that education and giving leaflets for karamunting plants received a positive response from the community, after being given materials and leaflets as well as interactive discussions, the community realized the importance of using herbal medicines as an alternative treatment and increasing body immunity.